174 Epilepsy Surgery in Infants Under 1 Year of Age. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Kumar, Ramesh Mohan; O'Neill, Brent R.; Koh, Susan; Laoprasert, Pramote; Knupp, Kelly; Park, Kristin; Chapman, Kevin; Handler, Michael H.
Abstract: INTRODUCTION: Infants with epilepsy often have a catastrophic course. There is a historical reluctance to operate in the very young, though experience is accumulating that persistent early seizures are detrimental. METHODS: Epilepsy operations performed on children under 1 year of age between 2002 and 2013 were reviewed for demographic information, seizure outcome, and surgical complications. RESULTS: Twenty-five patients were 18 days to 11 months at operation, the mean age 141 days, and median 99 days. Seventeen (68%) of these had seizures by the first 2 weeks of life. All had daily seizures and 80% had more than 10 seizures per day. Twenty-two had an abnormal MRI. Fifteen (60%) patients underwent hemispherotomy at initial operation, and 1 an anatomical hemispherectomy. Seven (32%) infants had grid placement followed by focal resection. One of these required a subsequent hemispherotomy. One patient underwent a frontal lobe resection with electrocorticography but required a subsequent grid placement with repeat resection. One had resection of a temporal DIGG. All underwent blood transfusions, but had no other complications. Two hemispherectomies were aborted because of bleeding, and completed at a subsequent operation. Focal cortical dysplasia was the most common pathology (10 patients, 45%) followed by hemimegalencephaly (7 patients, 32%). One patient each had hemispheric infarct, Tuberous sclerosis, Sturge-Weber, atypical Rhett syndrome, and cobolamine C deficiency. Mean follow-up was 53 months. Twenty-one patients (84%) are seizure-free, 10 (40%) on no anticonvulsant. One patient is Engle class 2, and the remaining 3 patients were Engel class 4, 1 of whom died with status epilepticus from the contralateral hemisphere. Shunts were required in 5 (20%). CONCLUSION: This large single-institution experience supports that infants with localization-related catastrophic epilepsy can have safe operations and excellent outcomes. There is no reason to delay intervention until they are older and have a longer-standing seizure burden.